Marketing Strategy of Oyster Mushroom (Pleurotus Ostreatus) in Maritengngae District, Sidenreng Rappang Regency (Case Study of Independent Mushroom Business) - Putri, Dian; Nurhapsa, Nurhapsa; Sriwahyuningsih, A. Erna (LaGeografia, 2021)
The purpose of this study was to determine the internal (strengths and weaknesses) and external (opportunities and threats) factors in Mandiri Mushroom’s business and to determine the right strategy for marketing oyster mushrooms in Mandiri Mushroom business. The analysis method used is the SWOT analysis. The result showed that internal and external factors based on weighting and rating obtained scores for the main strength factor in this Mandiri Mushrooms business werw the good quality of oyster mushrooms and the weakness namely the lack of venture capital. Meanwhile, the most supportive opportunity factor for marketing in this business is that it can compete with other oyster mushroom businesses and the threat factor that will be faced is the presence of pests that cause oyster mushrooms to not develop properly. The strategy that should be applied to this Mandiri Mushroom business based on the SWOT matrix is the Strengths-Opportunities (S-O) strategy, which is to try to use its main strengths to maintain the quality of oyster mushrooms so that they get the main opportunity, which is to compete with other oyster mushrooms businesses.